Patologi Sosial pada Novel Perempuan di Titik Nol Karya Nawal El-Saadawi - Lakda, Nirmawati; Hinta, Ellyana; Sartika, Eka (Ideas Publishing, 2024)
Many people move away from applicable norms and laws due to society's inability to face the challenges of globalization, this is called Social Pathology. This research aims to describe forms of social pathology from the criminal aspect which includes violence and abuse, as well as social pathology in the form of prostitution and mental disorders in the novel Perempuan di Titik Nol by Nawal el-Saadawi. In this research, the data was analyzed using Wellek and Warren's literary sociology approach which focused on the second study, namely the sociology of the content of literary works. The research results show that the novel Perempuan di Titik Nol has forms of social pathology including: crime in the form of violence and abuse, prostitution, and mental disorders